Pengaruh Artificial Intelligence dalam Menggantikan Peran Manusia di Dunia Kerja Ditinjau dari Peraturan Pemerintah No 33 Tahun 2013 Tentang Perluasan Kesempatan Kerja - Imtikhani, Najih; Nugroho, Any; Farina, Thea (Jurnal Sosial Teknologi, 2025)
The rapid development of Artificial Intelligence (AI) in Indonesia’s industrial sector presents both opportunities and challenges for the workforce. This study investigates the impact of AI on employment and examines whether its implementation aligns with Government Regulation No. 33 of 2013 concerning Employment Expansion. Despite AI’s potential to replace routine human tasks and increase unemployment, it also opens new job opportunities requiring complex skills and creativity. This research employs a normative juridical method, focusing on the analysis of existing labor laws, particularly Law No. 13 of 2003 on Manpower and Government Regulation No. 33 of 2013. Primary and secondary legal sources are critically examined to assess the regulatory framework’s adequacy in protecting workers’ rights amid AI adoption. The findings reveal that while AI can enhance efficiency and productivity, automation risks job losses, especially in routine tasks, necessitating comprehensive policies and training programs to prepare workers for this transition. The study underscores the urgent need for Indonesia to develop specific AI regulations to ensure legal certainty and social protection for affected workers. Policymakers should prioritize proactive training initiatives to foster workforce adaptability and enable harmonious coexistence between humans and AI in the labor market.